Peru : Rural Electrification - World Bank (Washington, DC, 2014)
The report analyzes rural electrification in Peru, in the context of social development, reviews the legal framework, and national rural electrification strategies, and examines opportunities for gaining access to electricity services. Regardless of the evident efforts recently made - the rural electrification coefficient increased from five percent in 1993, to twenty percent by 1997 - to improve rural access to electricity, much remains to be done, since six million households still have no access, aggravated by the fact that the majority of these people live in areas so isolated, that the likelihood to access the national grid, is not expected anytime soon. Furthermore, the majority of the rural population will most likely access electricity by using small isolated power supply systems, a questionable approach, since such systems are highly costly, and because they are seemingly unsustainable. Based on selection criteria, and survey results, the report identifies a case study on the management system in Chalan, reporting weaknesses such as vulnerability to interference by municipal authorities, social bias in tariff implementation, and uncertainty regarding poverty ownership. The National Electrification Plan calls for an increase of the electrification rate, expecting this increase will come from grid extension. And, although private concessionaires are expected to extend the grid, it is doubtful this will be applicable to rural electrification. International experience indicates the need to structure different institutional models, and financial delivery systems, not only in the construction of systems, but in the operation, and maintenance aspects.